ANALISIS PERASAAN SENANG (KEPUASAN) TERHADAP HASIL KERJA YANG DIUKUR MELALUI KOMUNIKASI, EFIKASI DAN PENGHARGAAN DIRI - Syamsi Mawardi; Arsid Arsid; Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Although feelings of pleasure are not defined as the main instrument in achieving performance, emotional involvement in work cannot be ignored. Invisibly, feelings dominate work attitudes and behavior, so that performance can be achieved. So paying attention to the factors of happiness and comfort at work must be considered by organizational management. This study aims to analyze the role of job satisfaction on improving performance by paying attention to the variables of communication, self-esteem, and self-efficacy. The research method uses causal associative with regression analysis techniques. In collecting data, a purposive sampling technique was used with a questionnaire as a research instrument. The results of the study indicate that satisfaction is a factor that is considered important by every employee. The reason is, work is not only a matter of making money, but as a place to interact between one person and another within the scope of business activities, then building good communication is a necessity, then having self-confidence is a capital in meeting the interests of the organization and the work environment. Statistically, the value of the contribution of the variables of communication, self-esteem, and self-efficacy is 0.162. This means that job satisfaction will increase with an estimated value of 16.2% if work communication is well developed and self-confidence is high.